Research on the Future Stability of Lamprey Based on Balanced Ecosystems - Zhang, Haowei; Xie, Yuhe (Transactions on Environment, Energy and Earth Sciences, 2024)
Lamprey is an ancient jawless fish known for its parasitic lifestyle. It has a unique ability to adjust gender ratios according to the environment and has had a profound impact on aquatic ecosystems. This interesting behavior, an adaptive and survival dance, invites us to delve deeper into the lives of these ancient creatures. The method used in this article simulates various aquatic habitats during a hypothetical period, including complex food chain interactions, availability of natural resources, population growth rate, and gender ratio of lamprey populations, among other key variables. This design allows for intricate interactions between ecosystem components and the sex ratio of lamprey populations. In order to evaluate how changes in the sex ratio of lampreys affect ecological dynamics, this study combines differential equation modeling with agent based modeling (ABM). By studying the interaction between the population, environmental resources, and reproductive rate of lampreys, this paper constructs a complex ecosystem simulation model and a comprehensive indicator to measure the ecological impact of different gender ratios.